PERANCANGAN SISTEM PAKAR DETEKSI PERTUMBUHAN TANAMAN SEMANGKA BERBASIS WEBSITE DENGAN CERTAINTY FACTOR - Tika Wulandari; Guna Yanti Kumala Sari Siregar Pahu; Dita Novita Sari (LPPM STMIK Pringsewu, 2018)
Expert system is a computer system that resembles the ability in making decisions of an expert and is part of artificial intelligence, hence with it to detect the growth of watermelon plants not everyone can know the growth of watermelon plants without an expert. The purpose of making these systems and applications to design and build Expert System for Watermelon Plant Growth Based Detection that uses certainty factor for use by farmers and the community to know the growth of watermelon plants without having to ask directly to expert experts, which can be said that the calculation of certainty factor on the characteristics of watermelon disease has a confidence level of 99.70%, because in this case Certainty Factor commonly used for decision making in the face of uncertainty of an event. This app is designed by beginning with SDLC and use case.